An effective algorithm for measuring diastolic artery diameters - HOEKS, A.P.G.; DI, Xu; BRANDS, P.J.; RENEMAN, R.S. (Archives of Acoustics, 1995)
The assessment of the distensibility or compliance of an artery by means of ultrasound involves the determination of the instaneous change in diameter as well as the initial diamter. The change in diameter as function of time (distension waveform) can be assessed accurately using sample volumes tracking the positions of the vessel wall-lumen boundaries. However, manual positioning of these sample volumes poses specific problems related to the pulsatile behavior of the lumen diameter. Intermediate storage of rf data over a few seconds will eliminate these problems but this will limit recording time and will increase hardware complexity. A method is described to detect the wall-lumen interface synchronously with ECG allowing for automatic positioning of the sample volumes. The user interference is restricted to a rough identification of the lumen position using the envelope of the received signal. Starting from within the lumen the sample volumes are forced outward until the local envelope exceeds a threshold dynamically adjusting to the peak value of the nearby vessel wall signals. The accuracy and reproducibility of the method has been verified using tubes with various internal diameters in a water tank and repetitive measurements from the common caroid artery of young presumed healthy subjects. The results show that the proposed method is consistent with a standard deviation of 150 micrometers which is on the order of the axial resolution of the ultrasound system used.